2015
DOI: 10.3389/fonc.2015.00015
|View full text |Cite
|
Sign up to set email alerts
|

Calreticulin as Cancer Treatment Adjuvant: Combination with Photodynamic Therapy and Photodynamic Therapy-Generated Vaccines

Abstract: Calreticulin is recognized as one of the pivotal damage-associated molecular pattern molecules alerting the host of the presence of distressed cells. In this role, calreticulin becomes exposed on the surface of tumor cells treated by several types of cancer therapy including photodynamic therapy (PDT). The goal of the present study was to examine the potential of externally added calreticulin for augmenting antitumor effect mediated by PDT. Recombinant calreticulin was found to bind to mouse SCCVII tumor cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 25 publications
(46 reference statements)
0
34
0
Order By: Relevance
“…The photosensitizer Temoporfin (Foscan) was provided by Biolitec Research GmbH (Jena, Germany). Other details of light delivery were described earlier [32]. At chosen intervals after PDT, some mice received 0.1 mg i.v.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The photosensitizer Temoporfin (Foscan) was provided by Biolitec Research GmbH (Jena, Germany). Other details of light delivery were described earlier [32]. At chosen intervals after PDT, some mice received 0.1 mg i.v.…”
Section: Methodsmentioning
confidence: 99%
“…The cells were then collected, exposed to X-rays (60 Gy), and delivered (2 × 10 7 per mouse) by peritumoral injection. Further details of experimental protocol were specified elsewhere [24,32]. Cyclophosphamide (Sigma) administration, 50 mg/kg dose i.p.…”
Section: Methodsmentioning
confidence: 99%
“…Currently, there are developments in both CD47 and CRT antibodies mainly for cancer therapy (Ho et al , ; Korbelik et al , ; Xiao et al , ). Human clinical trials of the anti‐CD47 cancer therapy begun in 2014, aiming at causing the immune system to wage a two‐pronged attack on cancer through both macrophages and T cells.…”
Section: Discussionmentioning
confidence: 99%
“…In this matter, Korbelik et al evaluated the effect of exogenously added CRT for improving the antitumor effect mediated by PDT [277]. They showed that antitumor immune response, prompted via PDT or PDT-generated vaccines, could be enhanced by externally added CRT and can be an operative adjuvant for cancer therapy with PDT [287].…”
Section: Therapies Combining Photodynamic Therapy-induced Icdmentioning
confidence: 99%